Investigation of the Sandblasting Pressure Effect on the Wear Properties, Surface Roughness, and Shear Bond Strength of Resin Nanoceramic and Zirconia CAD/CAM Restorative Materials - Elif İlgi Sancak; Elif Sevilay Yildirim; Neslihan Tekçe; Seval Başpinar Alper (Current Research in Dental Sciences)
Objective: Investigation of the influence of sandblasting pressure on the wear properties, surface roughness, and bond strength of resin nanoceramic and zirconia materials.Methods: 80-specimens with dimensions of 14 × 14 × 2 mm were obtained from Lava-Ultimate and Katana-Zirconia CAD/CAM materials. Four groups were formed according to the sandblasting pressure (control, 1-bar, 2-bar, and 3-bar). Sandblasting treatment was performed with 50-µm Al2O3 from a distance of 10-mm for 10-seconds at a pressure of 1, 2, and 3-bar. The weight loss caused by sandblasting was calculated and converted to volume loss. The surface roughness was evaluated with a contact profilometer. A randomly selected one specimen from each group was scanned using a non-contact profilometer. Composite rods were bonded to the surface of the materials with dual-cure adhesive resin. The shear bond strength test was performed. The data were analyzed using the Shapiro-Wilk test and two-way analysis ANOVA (P<.05).Results: The highest volume difference values for Lava-Ultimate were obtained in Group-3 (2.914±0.458). The highest Ra values were observed in Group-3 for Lava-Ultimate (2.620±0.121) and Katana-Zirconia (0.770 ± 0.106). Lava-Ultimate exhibited higher volume loss and Ra values than Katana-Zirconia at all sandblasting pressures. However, it showed higher SBS values (16.61±3.31) only in Group-1 (P<.05).Conclusion: Increasing sandblasting pressure affected the amount of wear and Ra values of Lava-Ultimate, while for Katana-Zirconia it only affected the surface roughness values. The increase in sandblasting pressure did not influence the shear bond strength values.Keywords: Resin nanoceramic, sandblasting pressure, shear bond strength, surface roughness, wear, zirconia